Crystallization kinetics, structure, and rheological behavior of poly(ethylene terephthalate)/multilayer graphene oxide nanocomposites. Issue 11 (28th August 2020) - Pinto, Gabriel M.; Silva, Giovanna da C.; Santillo, Chiara; Lavorgna, Marino; Maia, João M.; Fechine, Guilhermino J. M.
Abstract: This work aims to produce poly(ethylene terephthalate)/multilayer graphene oxide (mGO) nanocomposites via continuous melt mixing in twin‐screw extrusion, and to study the changes in crystallization and melt flow behavior. Three mGO contents (0.05, 0.1, and 0.3 wt%) were used. Differential scanning calorimetry analyses showed that at 0.1 wt%, mGO acted best as nucleating agent, increasing the crystallization kinetics as well as the melt crystallization temperature (Tmc ) by more than 20%. It was also observed that mGO increases the crystals perfection. The nucleating behavior was confirmed by X‐ray diffraction and small angle X‐ray scattering analyses, which showed a decrease in the composites' crystalline lamella thickness (lc ) and long period. X‐ray microtomography data confirms that this behavior is significantly affected by the mGO agglomerates distribution and specific surface area inside the polymer matrix. The rheological behavior was studied under two different conditions. It was noticed that under lower shear stresses the mGO particles hinder the polymer flow, increasing the composites viscosity and the pseudo‐solid character. However, under higher shear stresses, for example, when flowing through a die, the nanomaterial enters its "superlubricity state, " acting as a lubricant to the flow. This is industrially interesting, because it may allow the use of less severe processing parameters to produce the nanocomposites. Abstract :